UNDERSTANDING INKARUL HADITH IN THE ISLAMIC WORLD AND MOVEMENTS IN INDONESIA (The Hadith Department, Faculty of Ushuluddin and Islamic Thought, State Islamic University of Raden Fatah Palembang., 2022)
This study aims to examine and describe the notion of Inkarul Hadith in the Islamic World and the Movement in Indonesia by focusing on the history, schools, figures, teachings, arguments and responses of hadith scholars about Inkarul Hadith. as for this research using qualitative research with a historical approach. This research uses a library research or and analyzes the data with descriptive analysis. The results of the study show that Ingkar sunnah is an understanding or opinion of an individual or group that rejects the sunnah of the Prophet as the basis of Islamic law. The Sunnah in question starts from a valid Sunnah, both substantially; namely the practical sunnah of practice (sunnah 'amaliah), or formal sunnah codified by the scholars which includes deeds (qaulan), deeds (fi'lan), and the approval of the Prophet (taqriran). This understanding emerged as a small group (only a splinter) in the history of its development, so that this understanding could not develop and could not provide color in the discourse on the dynamics of the flow of thought in Islam. Because his understanding tends to weaken the joints in building Shari'ah Islamiyah. Thus, there is a need for enlightenment steps from the government and scholars to the ummah and Islamic groups with various and strategic aspects. so that this understanding cannot develop and cannot provide color in the discourse on the dynamics of flow of thought in Islam. Because his understanding tends to weaken the joints in building Shari'ah Islamiyah. Thus, there is a need for enlightenment steps from the government and scholars to the ummah and Islamic groups with various and strategic aspects. so that this understanding cannot develop and cannot provide color in the discourse on the dynamics of flow of thought in Islam. Because his understanding tends to weaken the joints in building Shari'ah Islamiyah. Thus, there is a need for enlightenment steps from the government and scholars to the ummah and Islamic groups with various and strategic aspects.